Islamic Banking in the Development of Creative Economy in Banten - Ikin Ainul Yakin (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
In the view of the MUI (Indonesian Ulema Council), especially the Banten Province MUI as an independent institution that has a role in the development of Islamic banking and the development of the creative economy in Banten, therefore it can be input and solution for economic growth and progress in Banten. Therefore, the importance of developing the creative economy in Banten is supported by several elements, including sharia banking which is quite developed in Banten Province. In this study, the author uses a qualitative research method based on the philosophy of postpositivism, used to examine the condition of natural objects, the author uses a type of field research with interviews and literature studies related to the discussion that author will examine, which is housed in the secretariat of the MUI Banten Province. From the study results, it can be concluded that the Islamic banking system will be an alternative solution for economic improvement and will be admired around the world if applied according to Islamic law. Islamic banking must continue to be strengthened by religious institutions with a Ta'awun system with good, professional, and honest management. It will reflect an economic system that is admired throughout the world. The role of the Banten Province MUI as an independent institution in the Banten province is very much needed, especially in the development of the creative economy in Banten by the vision, mission, and work program of the Banten Province MUI.